Metabolic Hydrolysis of Aromatic Amides in Selected Rat, Minipig, and Human In Vitro Systems - Bradshaw,P; Wilson,I; Upcott,Gill R; Butler,P; Dilworth,C; Athersuch,TJ (Scientific Reports, 2018)
The release of aromatic amines from drugs and other xenobiotics resulting from the hydrolysis of metabolically labile amide bonds presents a safety risk through several mechanisms, including geno-, hepato- and nephrotoxicity. Whilst multiple in vitro systems used for studying metabolic stability display serine hydrolase activity, responsible for the hydrolysis of amide bonds, they vary in their efficiency and selectivity. Using a range of amide-containing probe compounds (0.5–10 µM), we have investigated the hydrolytic activity of several rat, minipig and human-derived in vitro systems - including Supersomes, microsomes, S9 fractions and hepatocytes - with respect to their previously observed human in vivo metabolism. In our hands, human carboxylesterase Supersomes and rat S9 fractions systems showed relatively poor prediction of human in vivo metabolism. Rat S9 fractions, which are commonly utilised in the Ames test to assess mutagenicity, may be limited in the detection of genotoxic metabolites from aromatic amides due to their poor concordance with human in vivo amide hydrolysis. In this study, human liver microsomes and minipig subcellular fractions provided more representative models of human in vivo hydrolytic metabolism of the aromatic amide compounds tested.